The Political Economy of Inequality - Ackerman Frank (Island Press, 2000)
The disparity in wealth both within and between nations has grown rapidly in recent years, and is becoming an increasingly significant issue in attempts to deal with environmental problems - from international negotiations over climate change to local concerns about environmental justice.